Students Perspective on How to Construct Local Cultural-Based Ethnomathematics Problem Solving - Dwi Erna Novianti; Zaenuri; Wardono; Sugiman (UNNES JOURNAL, 2025)
Current mathematics learning shows that problem solving often remain procedural and are not closely connected to local cultural contexts. Students generally tend to seek answers directly without going through systematic stages of problem understanding and strategy planning. The purpose of this study is to analyze the problem-solving ability of a question in the social and cultural context of local wisdom in Bojonegoro Regency. The current study was qualitative descriptive through problem-solving tests and interviews in collecting the data. The test results are then analyzed and described in relation to their problem-solving ability following Polya's steps. The respondents of this study were 6th-semester students in which they were selected using a purposive sampling technique. Two subjects were selected, namely ST (subjects chategorized with high ability) and SR (subjects with low ability). The results of the study showed that the two subject had different ways in solving the problems in a question, where ST has structured ways in solving problems compared to SR who using Polya's steps. Another finding was that students found non-mathematical information beyond the mathematical information related to the problem. This non-mathematical information refers to the stories related to local cultural wisdom that inherent in the problem. It makes learning more meaningful and provides the students with new experiences. Contextual learning that incorporated ethnomathematics elements that acts as a bridge for the students in understanding interconnection among mathematics and their daily lives. This process comes regarding the respect for cultural diversification, especially to empower the students in the area of cognitive, social, emotional, and political. Through ethnomathematics approach, students' understanding of mathematical concepts can be reconstructed effectively. Based on these findings, further research need to be conducted regarding to the develop other indicators of problem solving. Abstrak Pembelajaran matematika saat ini menunjukkan bahwa proses pemecahan masalah masih sering bersifat prosedural dan terlepas dari konteks budaya lokal. Sebagian besar cenderung langsung mencari jawaban tanpa melalui tahapan pemahaman masalah dan perencanaan strategi secara sistematis. Tujuan dari penelitian ini adalah untuk melakukan analisis kemampuan pemecahan masalah pada soal dalam konteks sosial dan budaya kearifan lokal yang ada di kabupaten Bojonegoro. Penelitian ini merupakan penelitian deskriptif kualitatif dengan teknik pengumpulan data menggunakan tes pemecahan masalah dan wawancara. Hasil tes tersebut kemudian dianalisis dan dideskripsikan terkait dengan kemampuan pemecahan masalah dengan menggunakan langkah Polya. Subjek penelitian ini adalah mahasiswa semester 6 yang dipilih dengan menggunakan teknik purposive sampling. Terpilih dua subjek yaitu ST (subjek dengan kemampuan tinggi) dan SR (subjek dengan kemampuan rendah). Hasil penelitian menunjukkan bahwa kedua subjek memiliki perbedaan dalam menyelesaikan masalah, dimana subjek ST lebih terstruktur dalam menyelesaikan masalah dibandingkan dengan subjek SR dengan menggunakan langkah Polya. Selain itu, temuan penelitian yang lain adalah mahasiswa menemukan informasi non matematis di luar informasi matematis yang berkaitan dengan soal. Informasi non matematis yang dimaksudkan adalah cerita terkait budaya kearifan lokal yang ada pada permasalahan permaslahan. Hal ini menjadikan pembelajaran lebih bermakna dan memberikan pengalaman baru kepada mahasiswa. Pembelajaran kontekstual yang menggabungkan unsur etnomatematika berperan sebagai penghubung bagi siswa dalam memahami keterkaitan antara matematika dan kehidupan sehari-hari. Proses ini dilandasi oleh penghargaan terhadap keberagaman latar belakang budaya, yang bertujuan untuk memberdayakan mahasiswa secara kognitif, sosial, emosional, dan politis. Melalui pendekatan etnomatematika, pemahaman mahasiswa terhadap konsep-konsep matematika dapat dikonstruksi ulang dengan cara yang lebih efektif. Berdasarkan temuan ini, maka penelitian selanjutnya yag dapt dilakakan adalah mengembangkan indkator pemecahan masalah.